2020
DOI: 10.1016/j.numecd.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Predictive associations between lifestyle behaviours and dairy consumption: The IDEFICS study

Abstract: Background: Physical activity (PA) and sedentary behaviours (SB) are related with obesity and cardio-metabolic risk, however the literature is controversial regarding the effect of dairy consumption on the development of cardiovascular diseases (CVD) risk factors.Aim: To assess longitudinally the relationship between specific lifestyle behaviours (PA and SB) and dairy consumption in a sample of European children and adolescents. Methods:Children from the IDEFICS study were included in the analyses. Two measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Children who consumed milk and yogurt had a positive relationship with a combination of high physical activity and low sedentary behaviors over the years [39]. The most likely reason is the clustering of different lifestyle behaviors, such as physical activity, smoking, or dietary behavior [40].…”
Section: Discussionmentioning
confidence: 99%
“…Children who consumed milk and yogurt had a positive relationship with a combination of high physical activity and low sedentary behaviors over the years [39]. The most likely reason is the clustering of different lifestyle behaviors, such as physical activity, smoking, or dietary behavior [40].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is important to emphasize that the consumption of milk and dairy products promote adherence to the nutrient recommendations and may protect against the most prevalent non-communicable chronic diseases [8,9]. Similarly, in the NHANES study, found that milk was the top food source of energy in all ages [32].…”
Section: Contribution Of Food Groups To Energy Intakementioning
confidence: 99%
“…Likewise, Ortega et al studied the association between dairy consumption and dietary patterns and intake of selected nutrients in 7-11-year-old children and concluded that children who drank more milk also had better dietary patterns [9]. Santaliestra-Pasías et al concluded that the consumption of dairy products could be part of a healthy lifestyle, including physical activity and low time of sedentary behavior activities [8].…”
Section: Contribution Of Food Groups To Energy Intakementioning
confidence: 99%
See 1 more Smart Citation
“…The study found that European children with a healthy lifestyle, specifically regarding physical activity and sedentary behaviors over time, consumed more milk and yogurt. This study suggests that the protective effect of dairy products on cardiovascular diseases (CVD) could be related to the association between their consumption and specific lifestyle behaviors [15].…”
Section: Introductionmentioning
confidence: 99%